2017
DOI: 10.1016/j.soildyn.2017.07.022
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic behavior of fiber-reinforced soil under freeze-thaw cycles

Abstract: This research presents the dynamic behavior of fiber-reinforced soil exposed to freeze-thaw cycles. The series of dynamic triaxial tests were conducted on fine-grained soil mixed with different percentages of basalt and glass fibers subjected to freeze-thaw cycles. The results showed that after freeze-thaw cycles, with the addition of basalt and glass fibers, the damping ratio and the shear modulus increased at a constant confining pressure because of the increase of stiffness, but the shear modulus decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(13 citation statements)
references
References 28 publications
(43 reference statements)
1
12
0
Order By: Relevance
“…Relevant tests confirmed that the attenuation of elastic modulus, cohesion and internal friction angle induced by a freeze-thaw cycle can be inhibited by the treatment of short glass fibers [ 86 ]. Moreover, short glass fiber could also increase the shear modulus and damping ratio of the treated soil [ 87 ].…”
Section: Unconventional Materials Used In Soil Improvementmentioning
confidence: 99%
“…Relevant tests confirmed that the attenuation of elastic modulus, cohesion and internal friction angle induced by a freeze-thaw cycle can be inhibited by the treatment of short glass fibers [ 86 ]. Moreover, short glass fiber could also increase the shear modulus and damping ratio of the treated soil [ 87 ].…”
Section: Unconventional Materials Used In Soil Improvementmentioning
confidence: 99%
“…As a kind of fiber that widely exists in nature, they are widely used in various industries because of their low cost, easy access, and high yield. In this paper, we selected three fiber types commonly used in previous fiber-reinforced soil studies: glass fiber [ 27 , 28 , 29 ], polyester fiber [ 30 , 31 ], and hemp fiber [ 32 , 33 ]. For this purpose, a series of water absorption and unconfined compressive strength (UCS) tests were carried out to investigate the effects of these three different types of fibers.…”
Section: Introductionmentioning
confidence: 99%
“…Expansive soil, identified as unsuitable construction materials for engineering, is low-graded because of its inferior mechanical properties, such as low strength and high potential for swelling and shrinkage [1,2]. Due to seasonal environments, the cyclic volume change of expansive soil causes severe damage to the lightly loaded structures founded on them [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the dynamic behavior of soil is significantly influenced by the dynamic shear modulus and damping ratio [1], which indicates the importance to select the dynamic shear modulus and damping ratio of soil in the construction in the seasonally frozen soil area in the south of Heilongjiang Province, northeastern Inner Mongolia, and northwestern Jilin Province. At present, the characteristics of expansive soil under different environments and conditions have been reported.…”
Section: Introductionmentioning
confidence: 99%